From Home Kitchen to Digital Showcase: The Transformation of Aku Pisang MSME in Alue Krueng Village - Muhammad Reza Aulia; Utari Azrani; Khairun Nisa; Agatha Debby Reiza Macella; Rony Rahmat Hidayat Hasibuan; Irham Maulana (Universitas Ahmad Dahlan, 2026)
Background: Home-based food MSMEs in rural and disaster-prone areas often face limited product innovation, weak managerial routines, and restricted market access. Objective: This community engagement program aimed to transform Aku Pisang MSME in Alue Krueng Village by integrating product innovation, simple business management, appropriate production technology, and digital marketing. Contribution: This study contributes a process-based empowerment model that connects production readiness, cost control, and digital market activation within one staged intervention, thereby extending single-component MSME-upgrading approaches. Method: A four-month participatory learning-by-doing program was implemented through needs assessment, production standardization, bookkeeping and cost-based pricing mentoring, equipment introduction, and guided social media/e-commerce onboarding. Results: The program expanded product variants from two to six flavors, shifted production from irregular orders to planned routines, introduced cost-based pricing and simple bookkeeping, improved packaging consistency, and broadened market reach through online and offline channels. Conclusion: The integrated approach strengthened Aku Pisang's operational, managerial, and marketing capabilities and provides a replicable framework for empowering rural food-based MSMEs in vulnerable contexts.